In Vitro Antidiabetic Activity and Bioactive Ingredients of Apis mellifera and Apis dorsata Binghami Nest Extracts - Sibala, Henike; Naharia, Orbanus; Manampiring, Nonny; Mokosuli, Yermia Semuel (Universitas Labuhanbatu, 2023)
Indonesia ranks 7th out of ten countries with diabetes mellitus, which continues to increase yearly. Honeycomb is rich in secondary metabolites formed from plant resins (propolis) which contain alkaloids, flavonoids, saponins, tannins, steroids and triterpenes. The research aimed to analyze the comparison of flavonoid content and antidiabetic activity with the enzyme Î±-glucosidase In Vitro nest extract of A. mellifera and A. dorsata Binghami. The samples used were nests of A. mellifera from northern Toraja, southern Sulawesi and A. dorsata Binghami from Southeast Minahasa, North Sulawesi. Using 96% ethanol, HPLC method of flavonoid testing and in vitro antidiabetic activity testing using Î±-glucosidase enzymes. The flavonoid content results were based on the number of peaks produced and the retention time of A. mellifera produced 26 compounds, and A. dorsata Bingham produced 21 compounds. The results of in vitro antidiabetic tests with Î±-glucoside enzyme inhibitors obtained IC50 values from the nest extract of A. mellifera of 3.605 mg/L and the nest extract of A. dorsata Binghami of 4.992 mg/L. The extract from A. mellifera had better antidiabetic potential than that of A. dorsata Binghami, although the difference is insignificant.